Application of social media and ICT-tools in new and small business ventures. - Alvie, Asim (My University, 2012)
The current research emphasizes on various questions raised and deliberated upon by different entrepreneurs. It provides a valuable contribution to comprehend the importance of social media and ICT-applications. Furthermore, it demonstrates how to support and implement the management consulting and business coaching start-ups with the help of social media and ICT-tools. The thesis presents a literary review from different information systems science, SME and e-business journals, web articles, as well as, survey analysis reports on social media applications. The methodology incorporated into a qualitative research method in which social anthropological approaches were used to oversee the case study activities in order to collect data. The collaborative social research approach was used to shelter the action research method. The research discovered that new business start-ups, as well as small businesses do not use social media and ICT-tools, unlike most of the large corporations use. At present, the current open-source ICT-technologies and social media applications are equally available for new and small businesses as they are available for larger companies. Successful implementation of social media and ICT-applications can easily enhance start-up performance and overcome business hassles. The thesis sheds some light on effective and innovative implementation of social media and ICT-applications for new business risk takers and small business birds. Key words